Cadmium and Zinc Levels in the Soils and Oil palm Tissues from Long-Term Application of Phosphate Rock Fertilizers - Ali, Aini Azura (2010)
There are reports from temperate region regarding Cd accumulation in soils due to the application of phosphate rocks (PR) in agriculture soil. Oil palm plantations in Malaysia used phosphate rocks as the main source of P fertilizer since 1960s till the present time. There are speculations that this continuous and long-term application of phosphate rock may led to the accumulation of Cd in soil and then, increasing the availability of this element for plant uptake and thus, could enter human body via food chain. Zinc also is of increasing concern as this element can be found in PR as an impurity, and under natural condition, Zn to Cd ratio in PR is high. Therefore, this study was conducted to determine the Cd and Zn concentrations in soil and plant parts of three different ages (<10, >15, >20 years). To carry out this investigation, six soil series were collected from two well managed oil palm plantations (one in coastal and another in inland areas) which are of second generation of planting. Jawa, Selangor and Sedu Series were selected from coastal areas, while Munchong, Rengam and Segamat Series were collected to represent inland areas. Fronds and fruitlets were also collected along with the soils (paired sampling). Correlation study was done to determine the relationship between Cd and Zn in soils and soil properties and also with Cd and Zn in the plant tissue. There was no accumulation of Cd in all soil series but Zn accumulation was observed for Selangor and Segamat Series. Cadmium and Zn were highest in Segamat Series compared with the other soil series. Fruitlets show no increase in Cd and Zn concentrations but Jawa and Selangor Series show increasing values of Zn concentration in the fronds. Cadmium exceeded the Investigation Level for Malaysian soils of 0.3 mg kg-1 but Zn was below the investigation level of 95 mg kg-1. Cadmium and Zn concentration in fruitlets were below the Maximum Permitted Concentration (MPC) of 1 and 40 mg kg-1 for Cd and Zn, respectively, as stated in the Malaysian Food Act (1983) and Food Regulations (1985). Correlation study reveals that soil pH and clay content were the soil properties that control Cd and Zn concentration in soil. Cadmium in soil and soil solution most probably have contributed to the Cd concentration in fruitlet (edible part) whereas Cd and Zn in soil may influence the uptake of these elements by the oil palm tree. To verify the findings of the field study, Cd and Zn adsorption studies were carried out. Also, studies on pH effect on adsorption and competitive adsorption between Zn and Cd were conducted. This study involved all the six soil series except for adsorption envelope which was only done for the Segamat and Selangor Series. The highest Cd and Zn accumulation in Segamat Series had been proven by the adsorption isotherm. Cadmium adsorption was depressed by the presence of Zn, leading to the no accumulation of Cd in all the soils series. Increasing soil pH in Selangor Series, with increase of oil palm age, led to the accumulation of Zn in this soil series. The third study (glasshouse) was conducted to determine Cd content in oil palm seedlings planted in soil, fertilized with PR and amended with POME cake and lime, which are two common soil amendment used in the plantation. Also, the study was done to determine whether these amendments affect Zn and P uptake by the oil palm seedlings. Lime added in Jawa Series tends to decrease Cd content in the root as shown by the decreasing exchangeable fraction concentration with the increasing rates. Meanwhile, POME amendment caused exchangeable and water soluble Cd fractions concentration to increase with the increasing rates. However, there was no influence on the Cd content in plant parts. Meanwhile, Zn content increased in root and leaf as exchangeable Zn fraction also increased between the rates, and for P, the content increased in all plant parts. POME and lime added to Segamat Series tend to decrease water soluble and organic P fractions throughout the rates.